1988
DOI: 10.1080/15287398809531175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenytoin, ketamine, and atropine methyl nitrate in preventing neuromuscular toxicity of acetylcholinesterase inhibitors soman and diisopropylphosphorofluoridate

Abstract: Toxic manifestations of acetylcholinesterase inhibitors (AChE-I) include muscle twitching and muscle fiber necrosis, in addition to muscarinic manifestations of acetylcholine excess. The AChE-Is pinacolyl methylphosphonofluoridate (soman) or diisopropylphosphorofluoridate (DFP) were administered to rats to produce spontaneous muscle fiber discharges. Soman produced discharges that arose primarily from the central nervous system (CNS), while those due to DFP were generated from the peripheral nerves as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…There are reports on the adjuvant therapeutic effects of phencyclidine (PCP), for example derivative ketamine (Schuh, 1975;Cohen et al, 1974;Clinton et al, 1988;Mion et al, 2003), thienyl phencyclidine (TCP, tenocyclidine) and some of their derivatives in the medical treatment of soman poisoning (McDonough and Shih, 1993;Lallement et al, 1994;Carpentier et al, 1994;Lallement et al, 1998a;Gabrielewitz et al, 1980). The structure-activity of PCP has been discussed in terms of its 3-ring system: an aromatic ring producing an area of negative charge, a basic heterocyclic nitrogen ring bearing a localized positive charge and a cycloalkyl ring which is lipophilic in character (Vaupel et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…There are reports on the adjuvant therapeutic effects of phencyclidine (PCP), for example derivative ketamine (Schuh, 1975;Cohen et al, 1974;Clinton et al, 1988;Mion et al, 2003), thienyl phencyclidine (TCP, tenocyclidine) and some of their derivatives in the medical treatment of soman poisoning (McDonough and Shih, 1993;Lallement et al, 1994;Carpentier et al, 1994;Lallement et al, 1998a;Gabrielewitz et al, 1980). The structure-activity of PCP has been discussed in terms of its 3-ring system: an aromatic ring producing an area of negative charge, a basic heterocyclic nitrogen ring bearing a localized positive charge and a cycloalkyl ring which is lipophilic in character (Vaupel et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that ketamine protects against GD-induced neuropathology, while anesthetic doses of barbiturate increase GD toxicity. 60 64 It also has been reported that intramuscular treatment of scopolamine protects against CWNA exposure. 35 , 36 , 4145 , 65…”
Section: Discussionmentioning
confidence: 98%
“…It has been previously shown that ketamine protects against GD-induced neuropathology, while anesthetic doses of barbiturate increase GD toxicity. [60][61][62][63][64] It also has been reported that intramuscular treatment of scopolamine protects against CWNA exposure. 35,36,[41][42][43][44][45]65 In addition to the CNS anticholinergic effects, the mechanism of protection by aerosolized scopolamine may involve antisecretory effects and reduction in copious airway secretion and respiratory toxicity and peripheral nervous system effects.…”
Section: Gd Control (2x)mentioning
confidence: 98%
“…Although it increases oropharyngeal secretions (as do nerve agents), in vitro studies have shown that ketamine protects AChE; the in vivo signi®cance of this is not known. 27 The second phase, or`intermediate syndrome', 107 begins after the cholinergic phase and lasts 4±18 days depending on the de novo resynthesis rate of AChE (usually 1% of preexposure AChE function is recovered per day). This phase is characterized by muscle weakness, particularly of the diaphragm, and is associated with respiratory failure and cranial nerve palsies.…”
Section: Nerve Agentsmentioning
confidence: 99%